2016
DOI: 10.1111/jog.13105
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ormeloxifene versus oral contraceptive in the management of abnormal uterine bleeding due to uterine leiomyoma

Abstract: Ormeloxifene with its convenient twice-weekly dosage schedule was effective in treating AUB-L, with 72% of patients responding to 6-month treatment compared with 8% with COC, even though leiomyoma volume increased insignificantly with both ormeloxifene and COCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…28 Other side effects observed are giddiness, abdominal pain, headache and development of ovarian cyst noticed when Centchroman was given at a higher dose as a treatment trial for dysfunctional uterine bleeding. 29,30 In our study, 24 (40%) complained of scanty menses, 16 (26.67%) had delayed menses and 4 (6.67%) patients had absence of menses during therapy as the only side effects which may be attributed to the low dose and alternate day regime.…”
Section: Discussionmentioning
confidence: 46%
“…28 Other side effects observed are giddiness, abdominal pain, headache and development of ovarian cyst noticed when Centchroman was given at a higher dose as a treatment trial for dysfunctional uterine bleeding. 29,30 In our study, 24 (40%) complained of scanty menses, 16 (26.67%) had delayed menses and 4 (6.67%) patients had absence of menses during therapy as the only side effects which may be attributed to the low dose and alternate day regime.…”
Section: Discussionmentioning
confidence: 46%
“…Improvement in dysmenorrhea is also an added benefit with Ormeloxifene therapy as seen in the study where out of 22 only 1 patient reported dysmenorrhea after treatment. In the study by Kriplani et al, 14 improvements in dysmenorrhea with a reduction in the visual analog scale (VAS) score from 6.3 to 1.5 was observed on treatment with Ormeloxifene.…”
Section: Discussionmentioning
confidence: 97%
“…The appropriate time point to test efficacy will need to be considered, subject to the type and purpose of therapy. Medical treatments designed to rapidly reduce MBL tend to have short follow-up times of between 1 month and 12 months [44,[110][111][112][113], whereas surgical interventions, such the levonorgestrel intrauterine system and endometrial ablation, are designed for long-term reduction of MBL. Monitoring of menstrual loss has been reported for up to 5 years after surgery at various time intervals, depending on the study [59,106,107,114].…”
Section: Recognition Of Limitationsmentioning
confidence: 99%